THE IMPACT OF COVID 19 ON THE SELF –EFFICACY OF THE DRUZE TEACHERS IN AN ONLINE LEARNING ENVIRONMENT IN ISRAEL - Haj, Maysaa (E-Journal VFU, 2025)
This paper discussed the influence of the coronavirus on the efficacy of Druze teachers in Israel and proposed practical strategies to improve this efficacy. This qualitative study used structured interviews to collect data from 12 interviewees (6 male and 6 female teachers and principals). To analyze data, Braun and Clarke’s thematic approach (2006) was used. The findings of the study demonstrated that (i) the need to develop digital competence and continuous training of teachers, (ii) the importance of psychological and social support for teachers, (iii) the importance of innovation and bridging the digital divide. The study recommended following (i) developing digital and pedagogical skills through training on educational platforms, (ii) focusing on the needs of students after the coronavirus pandemic by providing psychological and emotional support, (iii) integrating life skills such as critical thinking, time management, and communication, (iv) professional development and community cooperation through the establishment of professional learning communities for teachers, strengthening partnership with parents and local institutions.